Integrasi Konsep Moderasi Beragama Dan Multikulturalisme - Rokib, Moh; Inayati, Mahfida; Maimun, Maimun (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This research aims to explore the integration of the concepts of religious moderation and multiculturalism as an approach in building social harmony in a diverse society. In an increasingly complex global context, especially in Indonesia, which is known for its religious, ethnic, and cultural plurality, religious moderation and multiculturalism are important strategies to prevent social conflicts and increase tolerance between religious communities. Through library research-based research, this study collects and analyzes literature from various academic sources, such as books, journals, and scientific articles that discuss both concepts theoretically and practically. This study found that religious moderation emphasizes the importance of a middle ground (wasatiyyah), which avoids extremism and radicalism in religion, while multiculturalism emphasizes acceptance and respect for cultural differences and beliefs. These two concepts share similarities in the principles of inclusivity, tolerance, and equality, which can be integrated within the framework of public policy, education, and social activities to strengthen national unity and global peace. The results of this research are expected to contribute to the development of policies that encourage social cohesion and answer the challenges of diversity in contemporary society. The integration of religious moderation and multiculturalism can be a solution to maintain a balance between religious identity and cultural diversity, as well as increase dialogue between different groups.